If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 6x + 21 Reorder the terms: 9 + 7x = 6x + 21 Reorder the terms: 9 + 7x = 21 + 6x Solving 9 + 7x = 21 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 9 + 7x + -6x = 21 + 6x + -6x Combine like terms: 7x + -6x = 1x 9 + 1x = 21 + 6x + -6x Combine like terms: 6x + -6x = 0 9 + 1x = 21 + 0 9 + 1x = 21 Add '-9' to each side of the equation. 9 + -9 + 1x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 21 + -9 1x = 21 + -9 Combine like terms: 21 + -9 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| -0.001x=0.002x | | 4+x^2=12-2 | | -24p+16q= | | -8(1+2d)= | | 8z+2z=9z-9 | | x^2=8-2x | | 33x+54=90 | | 8x^2-41x+5=0 | | -14(a+b)= | | -3x+15-2x+6x-18=3 | | g(4s+6)= | | -3x-y=-3 | | -7(1+f)= | | -9(r-4)= | | -m(x+3)= | | 12x^3+24x^2-15x=0 | | p(7-2g)= | | 2n+7(n-3)=6 | | 2*2/6= | | 0=-16x^2+14x+6 | | n-(-45)=90 | | 7(5y-8)= | | 9x=5x-4 | | 24+-72= | | 4=-16x^2+14x+6 | | 4=-16x^2+14+6 | | 8x+32+5x=20 | | -16x^2+8x+15=0 | | 3x-6=180 | | w^2+9w-10= | | 8x^2-16x=6x-12 | | 6*3.14x=27 |